2019
DOI: 10.1080/02614367.2019.1586981
|View full text |Cite
|
Sign up to set email alerts
|

An ecological-phenomenological perspective on multispecies leisure and the horse-human relationship in events

Abstract: The aim of the Leeds Beckett Repository is to provide open access to our research, as required by funder policies and permitted by publishers and copyright law. The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…To achieve this level of communication and some shared understanding requires a degree of partnership between horses and humans (Maurstad, Davis & Cowles, 2013). This partnership often develops over time, and is vulnerable to breakdown during periods of stress and in the face of unfamiliar environments and stimuli, such as might be experienced away on holiday (Dashper & Brymer, 2019). Some of these issues are explored further in the narratives presented below.…”
Section: Theorising Human-animal Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this level of communication and some shared understanding requires a degree of partnership between horses and humans (Maurstad, Davis & Cowles, 2013). This partnership often develops over time, and is vulnerable to breakdown during periods of stress and in the face of unfamiliar environments and stimuli, such as might be experienced away on holiday (Dashper & Brymer, 2019). Some of these issues are explored further in the narratives presented below.…”
Section: Theorising Human-animal Relationshipsmentioning
confidence: 99%
“…The horse may not want to step into a stream, for example, and may act to try and resist this by backing up or turning around. However, if the human really wants the horse to walk through the stream then the human has capacity to enforce this behaviour through various practices (Dashper & Brymer, 2019).…”
Section: Theorising Human-animal Relationshipsmentioning
confidence: 99%
“…She argues that there is a need for concentration on more equal, mutual wellbeing in such leisure environments, as there is currently a favouring of human experiences in cat shows. Dashper and Brymer (2019) introduce an ecological-phenomenological framework for understanding relationships between animate actors and their environment in and through leisure, by using the example of human riders and horses in the context of a pleasure ride leisure event. They underline the importance of considering all practices and interactions in relation to the environments in which they take place.…”
Section: Introduction To the Papers In The Special Issuementioning
confidence: 99%
“…Previously human-animal relations have focused around human consumption and utilization of animals for peoples' benefit; however, more recently, authors such as those indicated above, as well as Fox (2006), Bertella (2014), Davis and Maurstad (2016), Danby et al (2019), Dashper (2019), Dashper and Brymer (2019) have began to realize the significance of animals in their own right, as sentient beings, worthy of moral consideration. The shifting role of the horse in society is acknowledged by Dashper (2012Dashper ( , 2017 and more recently by the works of Dashper and Brymer (2019) and Sturød et al (2019) indicating that once it was considered a vital partner to humans in terms of agriculture and warfare as well particularly with reference to transportation; however nowadays, the horse plays a predominant partner within sport, leisure, and tourism, and horses are becoming increasingly popular as companion and therapy animals (Wolframm et al, 2013). Changing economies, societies, and technologies have transformed the predominant roles held in human life (Evans & Vial, 2015).…”
mentioning
confidence: 99%
“…The specific focus on horses is evident within this article, due to the fact that throughout history they have proven to have had varied roles within society. In contemporary society, the horse is a significant actor within the leisure, tourism, and events landscape, acting as a NBS, the result being a companion and a substitute for family members; furthermore, they contribute immensely toward emotional recreation (Danby et al, 2019;Kline et al, 2015;Notzke, 2019) although the body of work is beginning to formulate (Buchmann, 2017;Danby, 2018;Danby & Hannam, 2016;Dashper, 2015Dashper, , 2017Dashper, , 2019Dashper & Brymer, 2019;Gilbert & Gillett, 2014;Pickel-Chavalier, 2015;Notzke, 2019;Sturød et al, 2019).…”
mentioning
confidence: 99%